무전해 Ni-P/Nano Diamond(ND) 복합도금에서 초음파 분산시간이 피막특성에 미치는 영향 - 조진기; Jin Ki Cho; 유미선; Mi Sun Yoo; 강성군; Sung Goon Kang (대한금속·재료학회지, 45(9), 2007)
Composite coatings were prepared by co-depositing fine particles of metallic or non-metallic compounds with the metal matrix. With a newly developed nano powder, the nano particles strengthened composite coatings are increasingly attracting scientific and technological interest by virtue of their high hardness, lo friction coefficient and total inertness to any acid or other chemical attack. Among these ultra fine particles, ultra dispersed diamond particles are increasingly attracting considerable scientific and technological interest. However, commercially available powders of detonation nano diamond are complex conglomerates consisting of discrete levels of aggregation. In this work, experiments have been carried out to study the effect of ultrasonic treatment time on the mechanical properties and surface morphology of the electroless Ni-P/nano diamond(ND) composite coating. The results show that the nano-particles are uniformly distributed in the composite coating, and the microstructure of the composite coating is much finer and denser compared with the pure Ni plating.